2020
DOI: 10.21037/tlcr.2020.02.14
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of PD-1/L1 inhibitors for non-small cell lung cancer in front-line treatment: a Bayesian network meta-analysis

Abstract: Background: This Bayesian network meta-analysis (NMA) was conducted to compare efficacy and safety of programmed death 1/ligand 1 (PD-1/L1) inhibitors in previous untreated advanced non-small cell lung cancer (NSCLC) patients.Methods: Eligible studies evaluating first-line anti-PD-1/L1 based regimens in advanced NSCLC patients were included. Overall survival (OS), progression free survival (PFS), objective response rate (ORR), as well as treatment-related severe adverse events (tr-SAE) were synthesized within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Indirect comparison implied that ICI-containing treatments were significantly superior to ICI-free treatments in OS, partly consistent with conclusions of previous meta-analyses. 40 , 41 Among the 18 comparable treatments, the top 10 OS were all from ICI-based treatments, and all ICI-free treatments ranked in the bottom eight. In contrast to ICI, the current status of CT seems to be crumbling.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect comparison implied that ICI-containing treatments were significantly superior to ICI-free treatments in OS, partly consistent with conclusions of previous meta-analyses. 40 , 41 Among the 18 comparable treatments, the top 10 OS were all from ICI-based treatments, and all ICI-free treatments ranked in the bottom eight. In contrast to ICI, the current status of CT seems to be crumbling.…”
Section: Discussionmentioning
confidence: 99%
“…PC performed significantly better than PM in terms of ORR (OR 1.60, 95% CI 1.20-2.20), PFS (HR 0.52, 95% CI 0.37-0.71) but not for OS (HR 0.75, 95% CI 0.51-1.10) in patients with PD-L1 high expression (10). In addition, Liang et al found that PC was comparable to PM in terms of OS and PFS (HR = 1.01, 95% CI: 0.63 to 1.57 and HR = 0.59, 95% CI: 0.35 to 1.06) in patients with PD-L1 high expression by meta-analysis (7). Those results of meta-analysis were different or even opposite, which might be due to the inherent limitation such as the risk of systematic bias and confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of chemotherapy plus immunotherapy is not fully understood. However, there was evidence suggesting that chemotherapy can stimulate the antigenicity and immunogenicity of the host by enhancing antigen processing and presentation and by eliminating immune-suppressive myeloid derived suppressor cells (MDSC) and regulatory T cells (Tregs) (7,(23)(24)(25)(26). Meanwhile, Ramakrishnan et al proposed that chemotherapy may stimulate tumor cells to CTLs via the upregulation of mannose-6-phosphate receptors (MPRs), and autophagy may exert a tremendous influence in the immunogenic signaling during chemotherapy, which might contribute to the synergistic effect of chemotherapy and immunotherapy (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations